Persepsi Generasi Z Terhadap Kegiatan Pertanian Di Desa Tumani Kecamatan Maesaan Kabupaten Minahasa Selatan - Moonik, Raymon Toar; Waney, Nordy; Pakasi, Caroline Betsi Diana (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This research was conducted from November 2022 to June 2023. This research used 2 types of data, namely primary and secondary data. Primary data was obtained through direct surveys in the field through interviews with Generation Z in the village using a questionnaire. Secondary data was obtained from literature studies and agencies related to the data needed in the research. Sampling using purposive sampling method (intentionally). The population of the z generation in Tumani Village, Maesaan District, South Minahasa Regency was 209 people and 30 percent (63 people) were taken as respondents. The data analysis method used in this research is descriptive analysis using a Likert scale. The results of the research on Generation Z's Perception of Agricultural Activities in Tumani Village, Maesaan District, South Minahasa Regency have a good perception of agricultural activities. Generation Z's perception based on internal factors has a good perception. Generation Z thinks that working in the agricultural sector is sufficient to meet family needs, the agricultural sector is a promising job, agriculture in Tumani Village has the potential to be developed, working in the agricultural sector is based on the level of education and land area, although Generation Z is aware that agricultural activities have high business risks. . Generation Z's perception based on external factors has a good perception. Agricultural content on social media, families work in the agricultural sector, and the agricultural sector is widely developed to influence the perceptions of Generation Z, even though modern agricultural technology is currently still difficult to obtain.